From happiness to the good life (Journal of Parents and Teachers, 2014)
This article talks about how becoming happy people and how being happy requires personal effort although it is worth it. A smile, self esteem and personal strengths are measurable indicators of happiness. People confuse pleasure with gratification and none says that pleasure is a positive emotion, but it doesn’t last long and depends on external factors. Gratifications last longer and to get them one must work in their personal strengths.
Keywords: family and education; happiness; pleasure; gratification.